2021
DOI: 10.3390/psych3020009
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Gratitude, Wellbeing, Spirituality, and Experiencing Meaningful Work

Abstract: Poor mental wellbeing not only affects an individual and their family, but it also affects the workplace and the society as a whole. Consequently, it is crucial to investigate approaches that can promote a positive mindset in order to enhance wellbeing. This study aimed to explore the association between gratitude, wellbeing, spirituality, and experiencing meaningful work. A sample of 197 participants (69.5% female) completed measures of gratitude, experiencing meaningful work, spirituality, and several wellbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 76 publications
(122 reference statements)
2
15
0
Order By: Relevance
“…However, fear/guilt and negative emotions religious community did not correlate with dispositional gratitude. The obtained outcomes partially corroborate our assumptions and several previous findings (Ng and Chan 2015;Szcześniak et al 2019;Loi and Ng 2021). Given that gratitude is mentioned and promoted in religious texts (Ng and Chan 2015;Loi and Ng 2021), and can coexist with religious faith (Homan et al 2014), it is understandable that the positive experience of gratitude is positively associated with the feeling of being loved by God.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, fear/guilt and negative emotions religious community did not correlate with dispositional gratitude. The obtained outcomes partially corroborate our assumptions and several previous findings (Ng and Chan 2015;Szcześniak et al 2019;Loi and Ng 2021). Given that gratitude is mentioned and promoted in religious texts (Ng and Chan 2015;Loi and Ng 2021), and can coexist with religious faith (Homan et al 2014), it is understandable that the positive experience of gratitude is positively associated with the feeling of being loved by God.…”
Section: Discussionsupporting
confidence: 89%
“…The obtained outcomes partially corroborate our assumptions and several previous findings (Ng and Chan 2015;Szcześniak et al 2019;Loi and Ng 2021). Given that gratitude is mentioned and promoted in religious texts (Ng and Chan 2015;Loi and Ng 2021), and can coexist with religious faith (Homan et al 2014), it is understandable that the positive experience of gratitude is positively associated with the feeling of being loved by God. Moreover, based on their experimental study, Lambert et al (2009) have concluded that people who prayed daily to God declared higher levels of gratitude than those who were not praying.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, gratitude can promote positive cognitive and behavioral changes in athletes. Gratitude is a powerful, positive life emotion that shapes our core beliefs, improves physical and mental health, boosts happiness, optimizes emotional and affective states, enhances coping capabilities, maintains spiritual peace and harmony, induces pro-social behavior, and has both individual and social value ( Loi and Ng, 2021 ; Yang et al, 2021 ). The broaden-and-build theory of positive emotions also suggests that gratitude, as a positive emotion, can broaden an individual’s tendency to think and act, and that gratitude can also help individuals establish and strengthen social connections with others, thus forming good social networks ( Emmons and McCullough, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…In psychology, gratitude is defined as a transient, emotional state arising from a two-stage process: the recognition that a benefit has been received and the acknowledgment that such a benefit is derived from someone else's action (4)(5)(6)(7)(8). When gratitude is experienced more regularly over time, in the form of a more general disposition in noticing and appreciating positive aspects in the world, it is conceptualized as a personality trait more than an emotional state (9).…”
Section: Introductionmentioning
confidence: 99%
“…From an evolutionary perspective, it has been proposed that gratitude is functional to identify those who have demonstrated responsiveness to their needs and preferences in order to create bonds with them ( 11 ). In some cases, the source of recognized benefits or positive aspects in the world may also be attributed to impersonal or non-human sources like God, nature, or the universe, suggesting that gratitude could also be related to the concept of spirituality beyond that of interpersonal relationship ( 6 , 9 , 12 14 ).…”
Section: Introductionmentioning
confidence: 99%